2021
DOI: 10.1002/pssb.202100450
|View full text |Cite
|
Sign up to set email alerts
|

Energy Diagrams of Lanthanide Energy Levels in Perovskite‐Type Calcium‐Based Double Oxides Examined by X‐Ray Photoelectron Spectroscopy

Abstract: The energy levels of 4f ground states for trivalent lanthanide ions (Ln3+) in CaMO3 (M=Ti, Sn, Zr, Hf) are examined using X‐ray photoelectron spectroscopy (XPS). Some Ln3+ 4f energy levels referred to the valence band maximum (VBM), especially for Tb3+, are evaluated from the Ln3+ 4f states extracted by the difference XPS spectra between nondoped and Ln3+‐doped materials. The energy position of the zigzag curves for the Ln3+ 4f energy levels are referred to the Tb3+ 4f energy levels obtained from the XPS measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…The absorption spectrum of CZO shows an intense absorption edge at 210 nm, which is assigned to the host lattice (HL) absorption. No intense absorption was observed for CHO because the HL absorption of CHO is observed in the vacuum UV region . Because two major Eu 3+ PL peaks were observed at 595 and 615 nm in both samples, the PLE spectra for each PL peak were exhibited at the top and bottom, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The absorption spectrum of CZO shows an intense absorption edge at 210 nm, which is assigned to the host lattice (HL) absorption. No intense absorption was observed for CHO because the HL absorption of CHO is observed in the vacuum UV region . Because two major Eu 3+ PL peaks were observed at 595 and 615 nm in both samples, the PLE spectra for each PL peak were exhibited at the top and bottom, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…No intense absorption was observed for CHO because the HL absorption of CHO is observed in the vacuum UV region. 32 Because two major Eu 3+ PL peaks were observed at 595 and 615 nm in both samples, the PLE spectra for each PL peak were exhibited at the top and bottom, respectively. It has been already reported that Eu 3+ (A) gives the major PL peak at 615 nm due to the induced electronic dipole transitions from 5 D 0 to 7 F 2 states, whereas Eu 3+ (B) provides the major PL peak at 595 nm caused by the magnetic dipole transition from 5 D 0 to 7 F 1 states.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A similar phenomenon was observed previously in CaSnO 3 doped with Eu 3+ at A sites, which indicates the CT(A) excitation energy is close to the bandgap energy in these stannate samples. 60 In addition, the results for the absence of the HL excitation band in the shorter wavelength region evidently indicated that the ET from the HL to Eu 3+ (A) hardly occurred in the sample including almost only Eu 3+ (A). On the other hand, the spectral shapes of the codoped samples including almost only Eu 3+ (B), in Figure 6b (middle), are conspicuously different.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…The sublattice of SnO 6 octahedra in the perovskite-type SSO may form not only a 3D framework in the crystal structure but also a 3D network of Sn 5s orbitals in the electronic structure, which results in the formation of the CB for electron transport or semiconducting behavior. , Therefore, Eu (B) 5d and Sn 5s orbitals in the octahedral sublattice are expected to interact more easily than Eu (A) 5d and Sn 5s orbitals, implying that the ET from the CB to Eu 3+ (B) occurs more easily than that to Eu 3+ (A). The energy levels of Eu 3+ (A) 5d states are generally higher than the CB minimum (CBM) in stannates, but those of Eu 3+ (B) 5d states could become as low as CBM. The differences of the 5d energy levels between Tb 3+ (A) and Tb 3+ (B) were clearly observed in LaLuO 3, and the Tb 3+ (B) 5d levels become lower because of the stronger CF at B sites .…”
Section: Resultsmentioning
confidence: 99%
“…The PLE peak for the 4f–5d excitation in BLTO:Pr 3+ was obviously red-shifted against that in CLTO:Pr 3+ . Because the ground energy levels of Pr 3+ and Tb 3+ are usually analogous to each other in the electronic structure of similar HLs, the PLE spectral features will be also understood as reported in Tb 3+ -doped cases. Namely, the red shift of the PLE peak for the 4f–5d excitation in BLTO:Pr 3+ is ascribed mainly to the larger CF splitting of Pr 3+ 5d states at B sites, which is also deduced from the XANES spectra in Figure .…”
Section: Resultsmentioning
confidence: 95%